2017
DOI: 10.11606/issn.1678-4456.bjvras.2017.132572
|View full text |Cite
|
Sign up to set email alerts
|

Atualização sobre a epidemiologia de<i> Dirofilaria immitis </i>na América do Sul e no México: revisão de literatura

Abstract: Dirofilaria immitis (LEIDY, 1856; RAILLET; HENRY, 1911) is a parasite that is widely disseminated around the globe, with a higher prevalence in warm, humid climates. The first report of its occurrence in South America is from 1878 in Brazil. At that time, reports were scarce and difficult to retrieve -therefore, gathering them will facilitate recordkeeping over time. Four databases were searched (Scopus, MEDLINE, LILACS, and PubMed) and the search keywords were "Dirofilaria" or "heartworm" and the countries' n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
(31 reference statements)
1
3
0
Order By: Relevance
“…All our sampled canids were free-ranging and most of them were never confined, reducing, therefore, the probability of transmission of the filarioid, which could explain the low infestation detected in our study. Finally, although Dirofilaria immitis appears to be well established in neighboring countries (Cuervo et al, 2013), our survey confirms that Chile is probably free of this nematode (Bendas et al, 2017).…”
Section: Discussionsupporting
confidence: 61%
“…All our sampled canids were free-ranging and most of them were never confined, reducing, therefore, the probability of transmission of the filarioid, which could explain the low infestation detected in our study. Finally, although Dirofilaria immitis appears to be well established in neighboring countries (Cuervo et al, 2013), our survey confirms that Chile is probably free of this nematode (Bendas et al, 2017).…”
Section: Discussionsupporting
confidence: 61%
“…Canine infection with Dirofilaria immitis has been studied across the five regions of Brazil with different infection rates recorded in 14 out of 26 states (Bendas et al 2017). Therefore, it is known that rates can vary over time and according to environmental or socioeconomic conditions (Labarthe et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Dirofilariasis is a parasitic disease caused by filarial worm Dirofilaria immitis (Leidy 1856), also known as the heartworm (Bolio-Gonzalez et al 2007), affecting mainly domestic and wild canids (Batista et al 2008). Humans and felines, which may be accidental hosts, are more susceptible to infection in areas with high prevalence of the canine disease (Garcez et al 2006, Mirahmadi et al 2017, which is distributed all over the globe (Bolio-Gonzalez et al 2007, Bowman & Atkins 2009, Hou et al 2011, Simsek et al 2011, Montoya-Alonso et al 2015, Bendas et al 2017. It has been found in every geographical region of Brazil, with prevalence rates over the last decade ranging from 2.1% in Florianópolis, in the Southern state of Santa Catarina (SC), to 62.2% in Armação de Búzios, in the Southeastern state of Rio de Janeiro (RJ) (Silva et al 2008, Dirofilaria immitis infection in dogs in Algodoal Island, Brazilian Amazon Furtado et al 2009, Ogawa et al 2013, Labarthe et al 2014, Soares et al 2014, Ramos et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Severe disease includes signs of congestive right heart failure ( 4 ). An update on the South American seroprevalence showed that no infected dog has been reported in Chile and that in the other countries were the infection has been detected, prevalence rates range from 14.41% in Argentina to 1.6% in Colombia, 8.9% in Mexico, 5.5% in Peru and 15.2% in Venezuela ( 5 ). The overall prevalence of canine D. immitis infection in Brazil was 13.03% ( 6 ).…”
Section: Introductionmentioning
confidence: 99%